2022
DOI: 10.1093/nar/gkac807
|View full text |Cite
|
Sign up to set email alerts
|

A regulatory network comprising let-7 miRNA and SMUG1 is associated with good prognosis in ER+ breast tumours

Abstract: Single-strand selective uracil–DNA glycosylase 1 (SMUG1) initiates base excision repair (BER) of uracil and oxidized pyrimidines. SMUG1 status has been associated with cancer risk and therapeutic response in breast carcinomas and other cancer types. However, SMUG1 is a multifunctional protein involved, not only, in BER but also in RNA quality control, and its function in cancer cells is unclear. Here we identify several novel SMUG1 interaction partners that functions in many biological processes relevant for c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…most of the miRNAs in the Let-7 family, except let-7a-3, are oncogenes, which are involved in oncocyte cycle regulation and affect cancer cell migration and invasion. Numerous studies have shown that hsa-let-7b-5p functions as a tumor suppressor in cervical cancer, breast cancer and glioma [ 34 , 35 ].RiskScore combines clinical factors (age and stage) to further diagnose the survival risk of BC patients for clinicians. Some studies reported [ 36 ] that TNM stage and tumor size differed in metastatic and non-metastatic BC ( P < 0.001), suggesting that our model may be a good predictor of tumor metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…most of the miRNAs in the Let-7 family, except let-7a-3, are oncogenes, which are involved in oncocyte cycle regulation and affect cancer cell migration and invasion. Numerous studies have shown that hsa-let-7b-5p functions as a tumor suppressor in cervical cancer, breast cancer and glioma [ 34 , 35 ].RiskScore combines clinical factors (age and stage) to further diagnose the survival risk of BC patients for clinicians. Some studies reported [ 36 ] that TNM stage and tumor size differed in metastatic and non-metastatic BC ( P < 0.001), suggesting that our model may be a good predictor of tumor metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…SMUG1 knockdown leads to the accumulation of 5-hydroxymethyluridine in RNA, accompanied by a depletion of ribosomal RNA subunits [ 97 ], strongly suggesting that SMUG1 might have a biologically relevant specialized function in RNA quality control. SMUG1 is also required for the maturation of hsa-let-7b-5p [ 171 ] and the maintenance of the telomerase RNA component ( hTERC ) in mammalian cells [ 170 ], apparently by regulating levels of modified RNA bases at the 3′-end of hTERC RNA, a region known to be methylated at C323 and C445 [ 172 ]. In cells, SMUG1 deficiency led to a reduction in telomerase activity (although TERT expression was not compromised), telomere attrition, perturbed localization of Dyskerin, and fragile telomeres [ 170 ].…”
Section: Smug1 Canonical (Dna Repair) and Non-canonical (Rna Quality ...mentioning
confidence: 99%